Experimental Investigation of R744 Ejector Efficiency - Zhang Jinrui; Wu Jingyi; EIKEVIK Trygve Magne (Zhileng xuebao)
The performance of a new ejector is investigated experimentally in this paper. A range of different test points is tested in order to give an overall view of the ejector performance. The motive nozzle inlet temperature is from 19 ℃ to 31 ℃ and the gas cooler outlet pressure is from 6 MPa to 8 MPa. The test facility used in this experimental analysis is a two-phase ejector refrigeration system with R744 as a working fluid. The experiment results show that the ejector works more efficiently when the entrainment ratio changes from 0.4 to 0.8 and the pressure ratio is from 1.09 to 1.20 approximately. Moreover, the best efficiency, which can be achieved when the pressure ratio is 1.132 approximately, is 0.389. The fitted mass flow rate agree well with the experiment results. The experiment results provide a basis for application and design of ejector.